CHARACTERISTICS OF CURRENT SEROLOGICAL TESTS FOR ANIMAL BRUCELLOSIS - D.I, Baxriddinov; A.D, Ulug‘muradov (Research Focus International Scientific Journal, 2026)
This article provides a comparative assessment of diagnostic methods used for animal brucellosis and their advantages and disadvantages. It also analyzes the state of research on brucellosis in farm animals in Uzbekistan.